2021
DOI: 10.3390/diagnostics11020282
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Heavy Metals and Proteinuria and Chronic Kidney Disease

Abstract: Background: The prevalence of chronic kidney disease (CKD) is increasing annually in Taiwan. In addition to traditional risk factors, heavy metals contribute to the development of CKD. The aim of this study was to investigate associations among heavy metals and proteinuria and CKD in the general population in Southern Taiwan. We also explored the interaction and synergetic effects among heavy metals on proteinuria. Methods: We conducted a health survey in the general population living in Southern Taiwan betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 48 publications
3
37
2
1
Order By: Relevance
“…Mechanisms of cadmium-induced nephrotoxicity include tubular injury, especially in the proximal tubule, intracellular oxidative stress, interstitial fibrosis, and reduction in the number of viable nephrons [ 1 , 13 ]. In previous reports conducted in Taiwan, blood and urinary cadmium concentrations, which are commonly used surrogates of body cadmium burden [ 14 , 15 ], were also positively correlated with proteinuria and a risk for CKD [ 16 , 17 , 18 ]. Considering the high prevalence of CKD and end-stage renal disease, which reached up to 15% and 3587 per million population in 2018, respectively, the influence of environmental cadmium exposure on CKD is a topic of concern in Taiwan [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms of cadmium-induced nephrotoxicity include tubular injury, especially in the proximal tubule, intracellular oxidative stress, interstitial fibrosis, and reduction in the number of viable nephrons [ 1 , 13 ]. In previous reports conducted in Taiwan, blood and urinary cadmium concentrations, which are commonly used surrogates of body cadmium burden [ 14 , 15 ], were also positively correlated with proteinuria and a risk for CKD [ 16 , 17 , 18 ]. Considering the high prevalence of CKD and end-stage renal disease, which reached up to 15% and 3587 per million population in 2018, respectively, the influence of environmental cadmium exposure on CKD is a topic of concern in Taiwan [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The associations of BCL with other medical (including dialysis water contamination), demographic, environmental, and lifestyle factors in CKD patients were not proven in our study. There have been studies indicating that low-level environmental cadmium exposure has harmful effects on human health and complex interactions with other environmental contaminants; additionally, the blood cadmium elevation also deteriorates the risks and outcomes of CKD [ 8 , 20 , 22 , 27 ]. In our study, the median BCL of the total population was 6.36 nmol/L, which was higher than that in studies in the general Asian population (2.67–4.45 nmol/L) [ 12 ] and consistent with previous studies in dialysis-dependent patients [ 22 , 23 ], suggesting that CKD patients might be more vulnerable to low-level cadmium exposure in their daily lives and have a higher risk of cadmium accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, the prevalence of CKD approaches 15%, and prevalent cases of end-stage renal disease (ESRD) reached 3587 per million population in 2018, commonly recognized as the most prevalent in the world [ 18 , 19 ]. In addition, previous reports indicated that blood and urinary cadmium levels were positively correlated with proteinuria and the risk of CKD in Taiwan [ 20 , 21 ]. Furthermore, the association between the blood cadmium concentrations and risk of mortality in ESRD patients, including hemodialysis (HD) and peritoneal dialysis (PD), has also been observed [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high level of lead in the blood was related to proteinuria and eGFR < 60 mL/min/1.73 m 2 [9]. Exposure to arsenic, lead, and cadmium appears to be related to CKD occurrence [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, an animal study demonstrated that lead causes an inflammatory response, leading to CKD [8]. A high level of lead in the blood was related to proteinuria and eGFR < 60 mL/min/1.73 m 2 [9]. Exposure to arsenic, lead, and cadmium appears to be related to CKD occurrence [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%